How proximity and space matter: exploring geographical & social contexts of radicalization in Northern Ireland - Ylitalo-James, Emma; Silke, Andrew (Taylor & Francis, 2022)
The “specificity problem” is one of the longest running unanswered questions in research on terrorism. This problem focuses on the fundamental question as to why do only a few people radicalize when many appear to have been exposed to at least some of the same causes of radicalization? The current study seeks to help answer that question through comparative research with two sample populations in Northern Ireland. In-depth interviews were carried out with 17 former paramilitary members and 12 paramilitary sympathizers. The interviews explored factors which distinguished those who became actively involved with paramilitary groups versus those who did not. The results discussed here found that geographic proximity to intercommunity violence flashpoints/interfaces was strongly associated with increased paramilitary involvement. Thematic analysis found this effect was mediated by two additional factors: (1) levels of exposure to violence and (2) levels of community isolation. The findings are discussed in relation to the wider literature on radicalization.
Keywords: radicalisation; specificity problem; Northern Ireland; terrorism; paramilitarism; support for terrorism